Thalamohippocampal atrophy in focal epilepsy of unknown cause at the time of diagnosis. (5th November 2020) - Leek, N. J.; Neason, M.; Kreilkamp, B. A. K.; de Bezenac, C.; Ziso, B.; Elkommos, S.; Das, K.; Marson, A. G.; Keller, S. S.
Abstract : Background and purpose: Patients with chronic focal epilepsy may have atrophy of brain structures important for the generation and maintenance of seizures. However, little research has been conducted in patients with newly diagnosed focal epilepsy (NDfE), despite it being a crucial point in time for understanding the underlying biology of the disorder. We aimed to determine whether patients with NDfE show evidence of volumetric abnormalities of subcortical structures. Methods: Eighty‐two patients with NDfE and 40 healthy controls underwent magnetic resonance imaging scanning using a standard clinical protocol. Volume estimation of the left and right hippocampus, thalamus, caudate nucleus, putamen and cerebral hemisphere was performed for all participants and normalised to whole brain volume. Volumes lower than two standard deviations below the control mean were considered abnormal. Volumes were analysed with respect to patient clinical characteristics, including treatment outcome 12 months after diagnosis. Results: Volume of the left hippocampus ( p (FDR‐corr) = 0.04) and left ( p (FDR‐corr) = 0.002) and right ( p (FDR‐corr) = 0.04) thalamus was significantly smaller in patients relative to controls. Relative to the normal volume limits in controls, 11% patients had left hippocampal atrophy, 17% had left thalamic atrophy and 9% had right thalamic atrophy. We did not find evidence of a relationship between volumes and future seizure control or with other clinical characteristics of epilepsy. Conclusions: Volumetric abnormalities of structures known to be important for the generation and maintenance of focal seizures are established at the time of epilepsy diagnosis and are not necessarily a result of the chronicity of the disorder. Abstract : Leek et al . demonstrate that patients with a new diagnosis of focal epilepsy show evidence of atrophy of the thalamus and hippocampus. These findings challenge the idea that brain atrophy in focal epilepsy exclusively results from the chronicity of the disorder in medically refractory patients.